On Morphological Problems of the Stara Moldava Speech in Banatska Klisura: Field Report - Radovanović, Dragana I. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Stara Moldava is a micro area of speech in Banatska Klisura (Clisura Dunării) which is a subject of disputes in dialectology. As a contribution to the study of southern speeches in Romanian Banat, the paper analyses some significant morphological features of this speech by using the materials collected and recorded in the given area.